Research on the Relationship between Private Equity Funds Activity and M&A Market in Central and Eastern Europe and Bulgaria - Dimitrov, Nikolai (Research Papers, 2014)
Private equity funds are alternative instrument for financing international M&A deals on a global scale. Their activity in Central and Eastern Europe follows the global trends but with several regional specifics. This instrument has potential to complement the infrastructure of the financial market in Bulgaria.The current research aims to present the dynamics of private equity funds’ activity in Central and Eastern Europe and Bulgaria for the period 2003-2011. The thesis defended is that the private equity funds have significant role as an alternative for financing international M&A deals. Multifactor regression analysis is used as a quantitative research method. The independent variables are selected to correspond to the private equity funds’ activity and to the specifics of the country’s economy-these are the volume of M&A deals in Bulgaria, the dynamics of GDP and loan activity of the bank sector for the period 2003-2011.The results of the research confirm its aim. The activity of the private equity funds in Bulgaria are positively correlated to the volume of M&A deals and the loan activity of the bank sector for the period. This relationship follows the basic economic logic of the operational specifics and activity of private equity funds. The expectations that private equity trends in Bulgaria follow these in Central and Eastern Europe are confirmed.
Keywords: Private equity funds; Mergers and acquisitions; Financial sector; Correlation; Financial sponsors; Loan activity; GDP